The implications of the behaviour of patients in the illness-role on the psychosocial relationship of physiotherapists with their patients - A. J. van Rooijen (AOSIS, 1993)
In order for the physiotherapist to adopt a holistic approach in the treatment of her patients, it is necessary for her to bear in mind the patient's previous experience of the illness-role. This experience will influence the patient's behaviour in any subsequent illness-role and thus his interpretation of the role of the physiotherapist in the total treatment plan. It follows then that the physiotherapist should critically evaluate the behaviour of her patient in the illness-role while also evaluating the influence of her own behaviour on the patient in order to make treatment effective.